Characterization of microplastics in the septic tank via laser direct infrared spectroscopy. (1st November 2022) - Liu, Nana; Cheng, Shikun; Wang, Xuemei; Li, Zifu; Zheng, Lei; Lyu, Yaping; Ao, Xiuwei; Wu, Haiwen
Highlights: MPs in the septic tank were analyzed by laser direct infrared for the first time. The abundance of MPs in the septic tank is 2803 (1489–4816) particles/g dw. MPs of 34 different polymers were detected in the septic tank. MPs in sediments are large in number and one order of magnitude higher than scums. Distribution features of MPs are reflected in the number, type, size, and morphology. Abstract: Microplastics (MPs) are emerging pollutants that have been widely detected in the atmosphere, hydrosphere, lithosphere, and biosphere. Such wide spread of MPs indicates that the effective control in different environmental sectors is in an urgent need, and the first step in meeting this need is to identify the occurrence of MPs in the relevant environment. However, research on MPs in septic tanks has not been reported so far. This study investigated the distribution characteristics of MPs in septic tanks with a size detection limit of as low as 20 μm detected by laser direct infrared spectroscopy. Results showed that the number of MPs in the septic tank was reached 2803 (1489–4816) particles/g dry sludge, and the amount detected in the sediments was one order of magnitude higher than that in the scums. A total of 36 types of MPs were found in the septic tank, and 26 types were found in both sediments and scums, but the type in the scums was 21% higher than that in the sediments. The size was mostly 20–100 μm, accounting for 86.3% and 91.2% in the sediments and scums, respectively. Four shapes of MPs were detected in the septic tank, namely, fiber, bead, granule, and fragment. Our study revealed that septic tanks are both sinks and sources of MPs, which are reflected in the fact that MPs are not only large in number but also abundant in types. Thus, significant attention should be paid to septic tank-based microplastic pollution, which may lead to environmental and health risks without proper control and management. Graphical abstract: Image, graphical abstract